2007
DOI: 10.1134/s0006297907080068
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of matrix metalloproteinase-9 transcription in squamous cell carcinoma of uterine cervix: the role of human papillomavirus gene E2 expression and activation of transcription factor NF-κB

Abstract: Matrix metalloproteinase-9 (MMP-9) plays an important role in initiation and progression of squamous cell carcinoma (SCC) of human uterine cervix. Regulation of MMP-9 expression in such tumors is insufficiently studied. Involvement of the human papillomavirus (HPV) gene E2 and transcription factor NF-kappaB in the regulation of MMP-9 transcription has been shown in some model systems and types of malignant tumors. The present work was mainly designed to reveal a possible role of the HPV gene E2 and transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…MMP9 expression is regulated by NFκB [44], and in one study was shown to be correlated with NFκB activation in patients with squamous cell carcinoma of the uterine cervix [45]. Although no GWAS studies have found SNPs in MMP9 to affect breast cancer risk, many prior studies have published results that support an association between MMP9 and breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 expression is regulated by NFκB [44], and in one study was shown to be correlated with NFκB activation in patients with squamous cell carcinoma of the uterine cervix [45]. Although no GWAS studies have found SNPs in MMP9 to affect breast cancer risk, many prior studies have published results that support an association between MMP9 and breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculated that NF- κ B may be involved in the inhibition of MMPs by TQ in chodrocytes. Since other signaling pathways such as mitogen-activated protein kinase also play an important role in the regulation of MMPs, 39 further studies are needed to reveal the precise mechanisms that underlie the regulation of MMPs by TQ.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are detailed studies examining the role of E2 in regulating the expression of Matrix Metalloproteinase-9 (MMP-9) (Akgul et al, 2006; Behren et al, 2005; Gasparian et al, 2007; Muhlen et al., 2010), IL-10 (Bermudez-Morales et al, 2011), hTERT (Lee et al, 2002b), beta 4-integrin (Oldak et al., 2010; Oldak et al, 2004) and the splicing factor SF2/ASF (Mole et al, 2009). …”
Section: E2 Functionsmentioning
confidence: 99%